Działalność gospodarcza ziemian i leśników polskich w Wielkim Księstwie Poznańskim w XIX wieku - Ławniczak, Grażyna (My University, 2020)
Początki nowoczesnego leśnictwa w Wielkim Księstwie Poznańskim sięgają pierwszej połowy XIX wieku. Instrukcje gospodarcze majątków ziemiańskich z tego okresu zawierają zapisy o stosowaniu reguł zarządzania lasem. Tradycje utrzymania lasu – "zachowanie lasu w naturalnym stanie i nie eksploatowanie nadmierne..." przekazują staropolskie poradniki gospodarskie. Zasady urządzania lasu wprowadzane w Wielkim Księstwie Poznańskim opierały się początkowo na niemieckiej nauce leśnictwa i stosowane były przez leśników polskich wykształconych w Królewskiej Saskiej Akademii Leśnej w Tharandcie. Leśnicy poznańscy zatrudniani przez ziemian, przekazywali praktykę urządzania lasu, mając jednocześnie na uwadze podniesienie produkcji rolniczej, co należało do specyfiki polskich gospodarstw rolniczych XIX wieku. Działanie ziemian i leśników skutkowało konkretnymi osiągnięciami między innymi przy osuszaniu łęgów nadobrzańskich i zalesianiu piaszczystych nieużytków. Zapotrzebowanie na sadzonki drzew przyczyniło się do rozwoju szkółek przy majątkach ziemiańskich. Łączenie gospodarstwa wiejskiego i leśnego, wprowadzanie nowoczesnych metod gospodarowania wyróżniało majątki polskie. Wspólnymi siłami podnoszono skutecznie i trwale rolnictwo i leśnictwo, przemysł i oświatę poznańskiej prowincji. Upowszechnianie wiedzy rolniczej i leśnej należało do działalności statutowej Towarzystw Rolniczych zawiązywanych w XIX wieku. Na potrzeby poznańskiej pracy organicznej wydawano książki z dziedziny leśnictwa. Dzieło Henryka Cotty, założyciela Akademii Leśnictwa w Tharandt, w tłumaczeniu na język polski, wydane zostało pięciokrotnie w latach 1816-1837 przez Jana Żupańskiego w Poznaniu. W 1868 roku ukazał się Podręcznik leśnictwa autorstwa leśników poznańskich. Od 1866 roku leśnicy zrzeszeni byli w Wydziale Leśnym Centralnego Towarzystwa Gospodarczego w Poznaniu, a od 1908 roku w Towarzystwie Leśnym w Wielkim Księstwie Poznańskim.

The beginnings of modern forestry in the Grand Duchy of Poznań can be traced back to the first half of the nineteenth century. The then rules and recommendations for the estates of the local landed gentry included instructions and guidelines for sustainable forest management. Furthermore, the traditions and good practices in forest management, i.e. the "preservation of a forest in its natural state and avoidance of its excessive exploitation...", had been passed from generation to generation in old Polish farming, gardening and land resource management manuals. The general rules for forest planning and management introduced in the Grand Duchy of Poznań were initially based on German forestry science and developed patterns in German silviculture, and were used by Polish foresters who had been educated at the Royal Saxon Academy of Forestry in Tharandt. The foresters, employed by local landowners, transferred good practices in forest use and management, but did not overlook at the same time the necessity to improve agricultural production, which was a particular trait of Polish farms in the nineteenth century. The combined effort of the local landowners and foresters resulted in significant archievements, such as the successful land drainage of water meadows on the Obra River or forestation of sandy wastelands, among others. The demand for seedlings of trees contributed to the development of plant nurseries and plant farms attached to land estates. A skilful combination of agricultural and forest farms, the introduction of state-of-the-art methods for managing them was particularly outstanding in Polish landed estates of the time. Joint attempts were made to elevate, efficiently and lastingly, local agriculture, forest industry and education in the province. The promulgation of agricultural and forestry knowledge was one of the key statutory objectives of the Agricultural Associations established in the nineteenth century. A number of books on forestry were published for the particular needs of organic work in Prussian Poland. The work of Johann Heinrich Cotta, the founder of the Royal Saxon Academy of Forestry in Tharandt, was published in Polish translation by Poznań-based publisher Jan Żupański in five editions between 1816-1837. Thereafter, in 1868, Forestry Manual was published, authored by the local foresters. From 1866, all foresters were formally organised in the Forestry Section of the Central Economic Society in Poznań, and from 1908 in the Forestry Association in the Grand Duchy of Poznań.
Niniejszy artykuł był przedstawiony przez autorkę na V Konferencji naukowej "Las i Historia", Gołuchów, dnia 17 października 2019 roku. This article was presented by the author at the 5th Academic Conference "The Forest and History", Gołuchów on October 17, 2019.
Keywords: historia leśnictwa XIX wieku; praca organiczna; gospodarka leśna; history of forestry in the 19th c.; Greater Poland in the 19th. c; organic work; forest management (silviculture)